(untitled) (Semiárida, 2022)
The objective of the work was to evaluate in two wheat varieties ACA315 and SY100 the effect of different nitrogen fertilization strategies (A: S/fertilization, B: 200 Kg.ha-1 Urea in tillering; C: 140 Kg.ha-1 Urea in tillering + 20 N foliar) and the use and combination of different fungicide molecules (S/F: without fungicides, TT: triazole + triazole, ET: strobirulin + triazole and C-E-T: carboxamide + strobirulin + triazole) on the presence and severity of foliar diseases that affect yield and quality in two wheat cultivars. The severity of MA Drechslera tritici repentis decreased with the application of nitrogen fertilizer, and differences were recorded between fertilization strategies, achieving greater control with B. The low severity of MA in reproductive states did not allow differentiating the effect of fungicide molecules. The severity of RA Puccinia striiformis f. sp. tritici was greater in the fertilized treatments without registering differences between the fertilization strategies. There were differences in favor of the C-E-T fungicide with respect to the control without fungicide in the ACA 315 with B and in the SY100 with C. The fungicide molecules did not present differences between themselves in the RA control. The results of the work allow us to conclude that increases in fertilization levels increase yield and % protein. Directora: Figueruelo, Andrea Mariana Co-director: Funaro, Daniel Oscar